Term structure of profit rates of sukuk MATLAB stochastic simulation - Adesina-Uthman, Ganiyat Adejoke (Cambridge Scholars Publishing, 2015)
This book explores several non-traditional and under-researched fields in Islamic finance through its investigations into how the newly-emergent financial instrument Sukuk behaves in the broader field of finite-period financing and pricing in the market place. It provides readers with didactic information on the fundamental theories of term structure and in-depth information on this nascent financial instrument in the Islamic capital market. The book employs one and two-factor models of term